La reconstruction des édifices religieux en Basse-Normandie après la Seconde Guerre mondiale - Alain Nafilyan (In Situ)
The study begun for the purposes of legal protection in conformance with ancient memorials allowed to establish synthetic material global relative to the reconstruction of the religious buildings by replacing it in its historic and economic local context. The typological analysis revealed a big formal explosion offering very characteristic, architectural variety and experimentation of the stylistic hesitances in the architecture of the 1950s. The art of stained-glass window making found a privileged position through research always more plastic around the lighting of the church. The conclusion will try to bring in the form of synthesis a contribution to a legitimate interrogation: can we speak about a « style » of the reconstruction?